Impact of COVID-19 on Lao Migration Case Study: Migrant Workers from Savannakhet Province Return from the Kingdom of Thailand - Khemmarath, Sitha; Sengsouriya, Phoutthavong; Phothirath, Maninouth; Sengvilaykham, Bounthong; Thykeo, Satheun; Suikhamlar, Khampeang (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
In this study, the research team focused on studying the factors of attracting and pushing Lao workers in mobility to work in Thailand, to study the factors that influence the decision making if the situation gets better, to identify the career opportunities during the closure of the country, and the prospects after re-opening the country, as well as to study of solutions and workers’ requirement. The sample selection of respondents in this study was 995 migrant workers from the Kingdom of Thailand within 9 districts out of 15 districts in Savannakhet Province by using convenience sampling and snowball sampling methods. Mixed methods were used for analysis which included content analysis, logistics regression, and Chi-square. The results of this study revealed that attractive factors including the higher income and being accepted from social more (such as parents proudly, public face of family that be able to generate income for family, family situation get better and equal or more than people in the same village). Push factors are included the bad economy locally (low currency rate, difficulty to earn money) and employ position locally insufficient (unemployment, hard to find a job). Most of the types of workers are semi-skilled, unskilled, and skilled workers accounted, respectively. The factors influencing the return of migrant workers during an outbreak were because “to avoid infection and family members are encouraged to travel back”. Factors influencing the decision making to return or to stay when conditions improve including the education level of household head, average monthly income, age and hometown location. Worker's requirements in this study, firstly, they would like the state or relevant authorities to help them in finding a job for those who returned from Thai. Secondly, they need to have more factories, which led to having more job availability, the job application is difficult for them to apply for. In addition, increasing minimum wages is very concern and unlocking the country as soon as possible.